From Caries Progression and Restoration Failures to Periapical Lesions in the Era of Precision. (January 2020) - Leonardi, D.P.; Vieira, A.R.
Knowledge Transfer Statement: Dental research can be thought of as a continuum of clinical observations that are dissected in the laboratory with answers that can be brought back to the clinic to change patient management. We believe this is the case for the use of adhesive systems and outcomes of dental treatment. Clinical observations related to negative outcomes have been tested in the laboratory and solutions have been proposed, with more precise implementation of these solutions possible when genomic approaches are added. Here we elaborate on this process based on the observations that lead to an attempt to inactivate metalloproteinase activity by dentin crosslinking.